Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil - Silva, Gabriel S. C.; Roxo, Fabio F.; Souza, Camila S.; Oliveira, Claudio (Zootaxa, 2018)
We describe two new species of Corumbataia from Central Brazil. The new species are known from Rio Corrente, a tributary of the upper Rio Paraná basin. Furthermore, the two species are distinguished from congeners, mainly by the presence of a broad naked area without plates or odontodes on the dorsal portion of the snout. Additionally, the two new species described here can be distinguished from each other by the caudal-peduncle depth, number of infraorbitals plates series and by the general color pattern of caudal fin.